Healthcare experiences, wellbeing and mental health of people who have variations in sex characteristics in Ireland - Keogh, Brian; Higgins, Agnes; Doyle, Louise; Downes, Carmel; Monahan, Mark; De Vries, Jan; Begley, Thelma (Trinity College Dublin, 2025)
An intersex variation is an umbrella term used to describe people who have differences in internal reproductive organs, external genitalia, chromosomal, genes or hormonal levels which do not fit or align with how society defines male or female. Intersex variations are congenital and when detected at a young age, the person can receive medical, surgical, or hormonal interventions to reinforce sex assignment or align the physical body to a gender. For some people, life-saving medical interventions are necessary, for example, if a baby is born without the capacity to urinate or if hormone treatment is required. However, some interventions are not necessary for physical functioning and are performed to align the physical body to a gender.
PUBLISHED